Optimization of L-asparaginase production from endophytic bacteria isolated from the mangrove Rhizophora mucronata - ARIN NAFISATURRAHMAH; ARI SUSILOWATI; ARTINI PANGASTUTI (Smujo International, 2023)
Abstract. Nafisaturrahmah A, Susilowati A, Pangastuti A. 2023. Optimization of L-asparaginase production from endophytic bacteria isolated from the mangrove Rhizophora mucronata. Nusantara Bioscience 15: 279-287. L-asparaginase is an enzyme that hydrolyes L-asparaginase to L-aspartate and ammonia. L-asparaginase has the potential to treat acute lymphoblastic leukemia and other malignant cancers. So far, purified L-asparaginase from Escherichia coli and Erwinea chrysanthemi has been available and applied clinically in humans. However, this treatment has side effects such as allergy, cross-interaction, immune system stimulation, drug resistance, and nonspecific L-glutaminase activity. These side effects can be overcome by discovering new sources of L-asparaginase, which are serologically different but have similar therapeutic effects. This study aims to determine the optimal conditions of endophytic bacterial culture in producing L-asparaginase. Endophytic bacteria were screened using an M9 medium with asparagine as a substrate; the L-asparaginase-producing isolates showed pink zones around the colonies. Optimization of L-aparaginase production by endophytic bacteria is carried out by One Factor at A Time (OFAT). Optimization of enzyme production includes incubation time, temperature, pH, ammonium sulfate levels, and glucose concentration in the bacterial growth medium; determination of enzyme production by Nesslerization method. The results showed that 8 isolates could produce high L-asparaginase, 14 isolates had medium ability, 30 isolates had low ability, and 2 bacterial isolates did not produce L-asparaginase. Endophytic isolates were able to produce the highest L-Aparaginase under different optimal conditions. The optimal incubation time for endophytic isolates in this study was 60-84 hours, the optimal temperature was 37ºC, the optimal pH was 7, the nitrogen content was 0.25 mg/L, and the optimal glucose level was 3%.